Efficacy of Bay Leaf (Syzygium polyanthum) in Regulating Lipid Profile in Dyslipidemia Model Rats: A Systematic Review - Trisilya Mita Anggrek; Indri Safitri Mukono; Maftuchah Rochmanti; Citrawati Dyah Kencono Wungu (Universitas Airlangga, 2024)
Introduction: Cardiovascular disease is the leading cause of death in the world, more than any other disease. The leading cause of cardiovascular disease is dyslipidemia. Long-term use of simvastatin can cause other diseases. One of the medicinal plants known to have anti-cholesterol effects is a bay leaf (Syzygium polyanthum). This study aimed to determine how the administration of bay leaf extract regulates lipid profiles.Methods: This study used a systematic review based on PRISMA guidelines. Sampling in this study was done by collecting studies available in e-databases: PubMed and Google Scholar, with the inclusion criteria being experimental studies about the effect of bay leaf extract administration in regulating lipid profile in rats.Results: This study consisted of 10 experimental studies on rats. Eight studies showed an improved lipid profile, while two other studies did not show an improving lipid profile after the administration of bay leaf extract.Conclusion: Most studies revealed that bay leaf extract positively improves lipid profiles by lowering total cholesterol, LDL, and triglycerides, increasing HDL levels, and having antioxidant and anti-inflammatory effects.